ДОЛИННАЯ СИСТЕМА КОЛЫМЫ, ИСТОРИЯ И ФАКТОРЫ ЕЕ СТАНОВЛЕНИЯ - Патык-кара Н.Г.; Постоленко Г.А. (My University, 2003)
The recent Kolyma River drainage system is not uniform in structure. The tectonic uplift of Upper and Middle Kolyma area occurred as a background process through the Cenozoic, and the climatically forced incision and accumulation were the most critical factors affecting the fluvial series structure and sediment thickness. The impact of climatic factor is apparent throughout the whole Kolyma basin. Tectonic processes and repeated transgressions caused repeated transformations of Lower Kolyma channel system. Submerged part of Kolyma valley has a compound character; it became a unified fluvial system only in the Pleistocene.
Keywords: Pleistocene; 551.435.13(282.251); Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен